NEOPROTEROZOIC SAND WEDGES: CRACK FORMATION IN FROZEN SOILS UNDER DIURNAL FORCING DURING A SNOWBALL EARTH - Maloof A.C.; Kellogg J.B.; Anders A.M. (My University, 2002)
Thermal contraction cracking of permafrost produced sand-wedge polygons at sea level on the paleo-equator during late Neoproterozoic glacial episodes. These sand wedges have been used as evidence for high (=<54°) paleo-obliquity of the Earth's ecliptic, because cracks that form wedges are hypothesized to require deep seasonal cooling so the depth of the stressed layer in the ground reaches =<1 m, similar to the measured depths of cracks that form wedges. test counter hypothesis equatorial opened under a climate characterized by strong diurnal cycle and low mean annual temperature (snowball earth conditions), we examine crack formation in frozen ground subject periodic variations. derive analytical expressions relating newtonian viscosity potential depth, concluding will only soils with viscosities greater than ~1014 Pa s. We also show numerical calculations of crack growth in frozen soils with stress- and temperature-dependent rheologies and find that fractures may propagate to depths 3-25 times the depth of the thermally stressed layer in equatorial permafrost during a snowball Earth because the mean annual temperature is low enough to keep the ground cold and brittle to relatively great depths.
Keywords: ICE WEDGES; SNOWBALL EARTH; OBLIQUITY OF THE ECLIPTIC; NEOPROTEROZOIC; PERIGLACIAL FEATURES; PERMAFROST; PALEOCLIMATOLOGY; MARS; Precambrian::Proterozoic::Neoproterozoic; Докембрий::Протерозой::Неопротерозойская